Antibiofilm activities of protein kinase inhibitors against Salmonella enterica serovar typhimurium / Mohd Fakharul Zaman Raja Yahya - Mohd Fakharul Zaman , Raja Yahya (2018)

(untitled)
Salmonella enterica serovar Typhimurium (S. typhimurium) is an important biofilm producer which causes severe gastroenteritis in humans and other mammals. Many antibiotics have been tested to eradicate S. typhimurium infection, however, the gastroenteritis remains a major health problem while the application of known protein kinase inhibitor in combating S. typhimurium biofilm is still not well investigated. To address this issue, two protein kinase inhibitors namely dimethyl sulfoxide (DMSO) and afatinib were evaluated against S. typhimurium biofilm. It was demonstrated that both 32% DMSO and its combination with 3.2 μg/mL afatinib which was termed DMSOdiluted afatinib (DDA) were effective in killing biofilm cells, reducing biofilm biomass and chemically modifying extracellular polymeric substances (EPS) matrix. These antibiofilm effects were also observed in other biofilm forming bacteria. Of the two protein kinase inhibitors, DMSO was selected as the effective antibiofilm compound. To understand the possible molecular basis underlying the antibiofilm effect of DMSO against S. typhimurium biofilm, the protein profiles of whole cells and EPS matrix were investigated. Subtractive protein profile analysis recognized two unique protein bands (25.4 kDa and 51.2 kDa) of whole cells which were present only in control biofilm and not in 32% DMSO-treated biofilm. In turn, 29 and 46 proteins were successfully identified from the protein bands of 25.4 kDa and 51.2 kDa respectively. The protein band of 51.2 kDa was also observed to be uniquely present in 32% DMSO-treated EPS matrix. Three proteins were successfully identified from this EPS protein band. In the next step, protein interaction network analysis identified several biological processes such as glycolysis, PhoP-PhoQ phosphorelay signalling and flagellar biosynthesis to be significantly (p<0.05) inhibited by 32% DMSO. In addition, subtractive in silico analysis revealed that 41 out of 75 identified proteins from the whole cells were essential for survival of S. typhimurium and were non-homologous to human host, making them ideal therapeutic targets for biofilm control. Collectively, this study demonstrated the remarkable antibiofilm effects of DMSO against S. typhimurium biofilm and its molecular basis. These findings develop a new insight into how to combat diseases mediated by S. typhimurium biofilm.